2023
DOI: 10.1186/s12902-023-01336-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of response to ovulation induction using letrozole in women with polycystic ovary syndrome

Abstract: Background This study aimed to evaluate the predictive value of the initial screening characteristics of women with anovulatory polycystic ovary syndrome (PCOS) who did or did not respond to 2.5 mg letrozole (LET). Methods The clinical and laboratory characteristics of women with PCOS who underwent LET treatment were evaluated. Women with PCOS were stratified according to their responses to LET (2.5 mg). The potential predictors of their responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…A high pre-treatment AMH merits initiating OI with higher doses of CC or LET than used in ovulatory women. [ 50 51 52 53 54 ] Alternatively, gonadotropins may be more effective in inducing ovulation in such women. In the context of IUI, very high levels of AMH >10 ng/ml may predict a poor response even with gonadotropins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high pre-treatment AMH merits initiating OI with higher doses of CC or LET than used in ovulatory women. [ 50 51 52 53 54 ] Alternatively, gonadotropins may be more effective in inducing ovulation in such women. In the context of IUI, very high levels of AMH >10 ng/ml may predict a poor response even with gonadotropins.…”
Section: Discussionmentioning
confidence: 99%
“…[ 52 ] A small retrospective study further reported an AMH level of 9.78 as the discriminatory level beyond which cumulative ovulation rates were significantly lower. [ 53 ] Finally, in a large cohort study of women with PCOS using Gen II AMH assay, it was noted that women with higher AMH levels needed higher doses of CC or LET to achieve ovulation and the chances of ovulation reduced with increasing levels of AMH. [ 54 ] In vitro studies involving human granulosa cells suggest that the probable underlying mechanism is related to high AMH, as high AMH inhibits aromatase activity and reduces follicular sensitivity to FSH.…”
Section: A Nti -M Ullerian H ...mentioning
confidence: 99%
“…The association between ovarian reserve markers such as age, AMH, and bFSH and the ovarian response has been reported in patients with normal ovarian reserve [ 23 ].In addition, many studies have uncovered the remarkable precision of ovarian reserve markers in predicting poor ovarian response [ 24 ] and have established mathematical models to forecast ovarian sensitivity [ 25 , 26 ]. In infertile PCOS women receiving letrozole for ovulation induction, increased levels of baseline LH/FSH ratio, AMH, and free androgen index were found to be negatively associated with response to letrozole treatment [ 27 ]. Moreover, PCOS individuals with significantly higher circulating AMH levels were more likely to be resistant to exogenous Gn ovulation induction and required a higher starting dosage [ 28 ].…”
Section: Discussionmentioning
confidence: 99%